Soldats hongrois en Palestine : lutte à côté des Ottomans contre les Britanniques, 1916-1918 - Ferwagner, Peter Ákos (Études sur la Région Méditerranéenne, 2022)
In May 1916, about 800, mostly Hungarian soldiers arrived in Ottoman Palestine. The Hungarian artillerymen organized in two batteries took part in the second attack by the Turks against the Suez Canal in the following period. In the spring of 1917, on the side of their Turkish and German allies, they fought fierce battles with the British in southern Palestine (first and second battles in Gaza). In late 1917 and during 1918, advancing British troops inflicted heavy losses on them in Palestine and Syria. After the ceasefire, the remaining troops were repatriated to Hungary via Constantinople and Trieste.